Analysis of smash forehand badminton strutting at the age of 9-14 years at gemilang badminton club samarinda - Aryapradana, C. A.; Cahyono, D.; Buhari, M. R. (International Journal of Humanities and Social Science, 2023)
This study aims to determine how good the accuracy of the forehand smash is at the age of 9-14 years at Gemilang Badminton Club Samarinda. This research is a quantitative descriptive study that aims to explain the accuracy of the forehand smash at Gemilang Badminton Club Samarinda. The data collection technique in this study used the smash. The population in this study amounted to 20 people, the sample taken was 12 people at Gemilang Badminton Club Samarinda using purposive sampling, from a total of 20 athletes. Data analysis uses descriptive percentages and uses SPSS assistance. Based on the overall results of the study of 12 athletes in the "good" category there was 1 person (8.3%), in the "enough" category there was 1 person (8.3%), in the "poor" category there were 10 people (83, 3%). So it can be concluded that the accuracy of the forehand smash at Gemilang Badminton Club Samarinda averages 16.25, so it is in the unfavorable category.